Statistical Analysis of Parental Involvement on Students’ Academic Achievement - Choudhary, Satyanarayan (NPRC Journal of Multidisciplinary Research, 2025)
Background: Parental engagement in education is commonly accepted as an important factor that determines the success of students academically. Although there is wide-ranging research to support such a relationship everywhere in the world, contextual elements such as socioeconomic differences, cultural beliefs, and institutional frameworks might impact its dynamics. In Nepal, specifically the Kathmandu Valley with its blend of public, private, and international schools, how parental engagement affects academic outcomes is not well studied. This study addresses this gap by examining the association between different parental involvement constructs and student outcomes in this unique school setting. Objective: This study aims to establish the connection between parental involvement and the academic performance of students in schools around Kathmandu Valley. Specifically, it examines the impact of parental expectations, direct academic help, family communication, and difficulty perceptions on academic achievement while controlling for socioeconomic moderators. Methods: A correlational study design consisting of 200 parents was utilized with a quantitative design, where data were collected from standardized questionnaires. Parental involvement, expectations, family interaction, and perceived difficulties were variables assessed on a 5-point Likert scale. School performance was collected from self-reported grades. Data analysis was conducted using SPSS with Pearson correlation and hypothesis testing (α = 0.01) for statistical significance. Findings: The findings revealed significant positive correlations between parental challenges (r = -0.021, p = 0.771), parental engagement (r = 0.326, p < 0.01), parental expectations (r = 0.292, p < 0.01), and family interaction (r = 0.240, p < 0.01) with academic achievement. Parental challenges were found to have no significant correlation (r = -0.021, p = 0.771). Demographic analysis found that younger parents who were more educated had greater engagement rates. Conclusion: The study confirms that active parental participation leads to better academic achievement in Kathmandu Valley schools, while socioeconomic and institutional mediators may intervene. Policymakers must ensure that interventions guarantee parental participation, particularly in public schools, via workshops, online forums, and community-based projects. Novelty: This research provides new insights into parental participation in Nepal’s diverse educational landscape, as opposed to foreign studies that propose a wide proportion of parental difficulties. It also provides empirical data for building localized education policy.